Static and fatigue behavior of shear connectors for a steel-concrete composite girder. (August 2019) - Deng, Wenqin; Xiong, Yingqian; Liu, Duo; Zhang, Jiandong
Abstract: As the key part of a steel-concrete composite bridge, the mechanical properties shear connectors that have direct impacts on the bearing capacity of the whole bridge. Angle connectors and twin-perfobond rib (T-PBL) connectors are commonly used in long-span steel-concrete composite bridges. Considering the convenience of construction, a new type of shear connector, the channel connector, is proposed. Push-out tests on three groups of 12 shear connector specimens under monotonic and repeated loads were carried out, and the static and fatigue behavior of the three different shear connectors were compared and analyzed. The results show that the ultimate bearing capacity of channel connectors is the largest, while that for the angle connectors is the second largest and that for T-PBL connectors is the smallest. With the increase in cyclic loading times, the ratio of residual deformation to plastic deformation shows a significant upward trend. The deformation recovery ability of the specimens decreases gradually, and the stiffness deteriorates continuously. The stiffness degradation of channel connectors is the slowest, and the stiffness degradation of angle connectors and T-PBL connectors is faster. The energy dissipation of T-PBL connectors is the largest, while the energy dissipation of angle and channel connectors is the same. The channel connectors proposed in this paper can be used as good shear connectors in steel-concrete composite bridges because of their strength improvement and their certain energy dissipation capacity. In addition, the 3D non-linear finite element models based on the three kinds of shear connectors is established to simulate the whole loading process by using the general finite element software ABAQUS. The results of finite element analysis are in good agreement with the experimental results, which can be used as a powerful supplement to the experimental research. Hightlights: A new type of shear connector for a steel-concrete composite girder bridge, the channel connector, is proposed. Push-out tests on three type shear connectors under monotonic and repeated loads were carried out. The initial stiffness of specimens under repeated loading is not significant compared with monotonic loading. The channel connectors are suitable for a steel-concrete composite girder because of their good mechanical properties.